Comparison of Capture Power of Wajanbolic Antenna with Parabolic Directional Antenna to the Distance of Capture Wireless LAN Signal 2.4 GHz - Yoliadi, Dodi Nofri (Universitas PGRI Kanjuruhan Malang, 2022)
The wokbolic antenna is used to capture the 2.4 GHz wireless LAN signal. The reflector is made of a frying pan. Focus on using a foil-lined paralon pipe. At the focus is given a USB adapter to capture the signal reflected by the reflector. To see the feasibility of a tool needs to be compared with equipment that has a standard data sheet. So a research was conducted by comparing the capture power of the wokbolic antenna with a directional parabolic antenna. The research method used is a real experimental method, namely an experimental signal strength measurement of both antennas at the same location, altitude under LOS conditions. From the results of experiments conducted at five distances: at a radius of 50 meters, 73 meters, 120 meters, 150 meters, and 290 meters. The farther the capture distance, the smaller the received signal, this happens to both antennas. After the data is obtained in the form of signal strength, then the antenna gain is calculated. The results of the antenna gain calculation show the difference between the gain of the wokbolic antenna and the directional satellite dish. To see if the difference in antenna gain is significant, it is analyzed by t-test. From the t test, it turns out that t count is greater than t table, it can be concluded that the difference in antenna gain is not significant.